THE STRATEGY OF #METOO MOVEMENT TO FIGHT FOR THE RIGHTS OF THE VICTIMS OF SEXUAL HARASSMENT IN SOUTH KOREA - Yana Dwifa Saraswati; Najamuddin Khairur Rijal; Shannaz Mutiara Deniar (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
This study discusses the adoption of the #MeToo Movement in South Korea in 2018 as one of the movements to reduce the problem of sexual harassment that still occurs in South Korea. The number of cases of sexual harassment in South Korea is still high this is due to the culture they still follow which then hinders any resolution or reduction of the number of cases of sexual harassment. This study uses a qualitative-descriptive research method, with data collection from a literature study. This study then discusses the strategies used by this movement with the aim of fighting for the rights of victims that have been taken for a long time. The results of the study found that the #MeToo Movement used a strategy of visibility and audibility in the concept of global civil society to voice the voices of victims and the aspirations of their supporters so that there would be beneficial changes for victims. The strategy of visibility and audibility is used so that their voices can be seen and heard directly by the community and the government.Penelitian ini membahas diadopsinya gerakan #MeToo di Korea Selatan pada tahun 2018 sebagai salah satu gerakan untuk mengurangi permasalahan pelecehan seksual yang masih banyak terjadi di Korea Selatan. Angka kasus pelecehan seksual di Korea Selatan masih tinggi hal ini disebabkan oleh budaya yang masih mereka ikuti yang kemudian menghambat adanya penyelesaian atau pengurangan terhadap angka kasus pelecehan seksual. Penelitian ini menggunakan metode penelitian kualitatif-deskriptif, dengan pengumpulan data studi kepustakaan. Penelitian ini kemudian mendiskusikan bagaimana strategi yang digunakan oleh gerakan ini dengan tujuan untuk memperjuangkan hak-hak korban. Hasil penelitian menemukan Gerakan #MeToo menggunakan strategi visibility dan audibility dalam konsep global civil society untuk menyuarakan suara korban dan aspirasi para pendukung agar adanya perubahan yang menguntungkan bagi korban. Strategi visibility dan audibility digunakan agar suara mereka dapat dilihat dan didengar secara langsung oleh masyarakat maupun pemerintah.